2019
DOI: 10.1177/8756972819877782
|View full text |Cite
|
Sign up to set email alerts
|

Crafting Project Managers’ Careers: Integrating the Fields of Careers and Project Management

Abstract: Project managers experience unique careers that are not yet sufficiently understood, and more people than ever before are pursuing such careers. The research on project management and careers is therefore urgently needed in order to better understand the processes and systems shaping the careers of project managers. We address this gap by reviewing several key career theories and constructs and examining how these are mobilized to understand project managers’ careers in existing research. Our main conclusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 116 publications
(169 reference statements)
1
78
0
4
Order By: Relevance
“…There has been limited research on project management careers (Bredin & Söderlund, 2013; Keegan et al, 2018), but interest is growing (Chipulu et al, 2017), with recent calls by scholars (Akkermans et al, 2020) for more extensive research in this area. Project management has traditionally been viewed as an ‘accidental profession’ (Darrell et al, 2010; Pinto & Kharbanda, 1995; Richardson et al, 2015) with individuals finding themselves “rolling into the profession” (Havermans et al, 2019, p. 346), with the role of project manager often “thrust upon [them] rather than being sought” (Pinto & Kharbanda, 1995, p. 216).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been limited research on project management careers (Bredin & Söderlund, 2013; Keegan et al, 2018), but interest is growing (Chipulu et al, 2017), with recent calls by scholars (Akkermans et al, 2020) for more extensive research in this area. Project management has traditionally been viewed as an ‘accidental profession’ (Darrell et al, 2010; Pinto & Kharbanda, 1995; Richardson et al, 2015) with individuals finding themselves “rolling into the profession” (Havermans et al, 2019, p. 346), with the role of project manager often “thrust upon [them] rather than being sought” (Pinto & Kharbanda, 1995, p. 216).…”
Section: Introductionmentioning
confidence: 99%
“…Recent calls to examine career entry routes into the project management profession (Chipulu et al, 2017; Klein & Aubry, 2017), and how project managers’ careers evolve (Akkermans et al, 2020), highlight that investigation of this new undergraduate degree pathway is timely. A ‘chosen’ career in project management accessed through the higher education route comes with a unique challenge (not found in the traditional accidental career entry route) in terms of work readiness; in other words, the extent to which graduates with undergraduate project management degrees are prepared for work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, project managers still depend on their employers for career opportunities and competence development although, according to some authors (Bredin & Söderlund, 2011), employers often struggle to offer clear career paths and developmental opportunities. Despite this increasing importance and peculiarity within occupational groups, project management is an under-researched occupational domain into the careers literature and more research is needed to understand how project managers develop, construct, conceptualize, or experience their careers (Akkermans et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More in detail, as for recent studies, boundaryless careers were found to be associated with higher career autonomy and lower career insecurity (Colakoglu, 2011), higher objective career success (Sammarra et al, 2013; Volmer & Spurk, 2011), higher active coping, and external support seeking (Briscoe et al, 2012). Nevertheless, it must be noticed that this does not seem to be the case for project management, where boundaryless careers have received considerably greater coverage (Akkermans et al, 2019).…”
Section: Introductionmentioning
confidence: 99%